Epilepsy and the “dark” literature of the Greek novelist Demosthenes Voutyras: an outstanding epileptic personality - Patrikelis, Panayiotis; Messinis, Lambros; Folia, Vasiliki; Nasios, Grigorios; Alexoudi, Athanasia; Verentzioti, Anastasia; Korfias, Stefanos; Kimiskidis, Vasileios; Gatzonis, Stylianos (Arquivos de Neuro-Psiquiatria, 2023)
Background The role of temporal lobe epilepsy (TLE) in determining personality traits and neurobehavioral symptoms, collectively known as the interictal behavioral syndrome (also known as Geschwind syndrome or “Gastaut-Geschwind syndrome”), as well as the syndrome's association with the particular artistic expression of many epileptic litterateurs are well known in neurology and psychiatry. A deepening of emotionality along with a serious, highly ethical, and spiritual behavior have been described as positive personality changes among patients with chronic mesial-TLE.Objectives Our narrative-based clinical hypothesis aims at contributing to the ongoing debate on the association between TLE and artistic expression, as well as the latter's supposed implication for epileptology in general and the neuropsychology of epilepsy in particular.Methods Through an analysis of the biography, language, and literary work of Greek novelist Demosthenes Voutyras, we hypothesize that his mystical and dark writing style could be attributed to medial temporal interictal dynamics.Conclusions We suggest that the psycholiterary profile of Voutyras is consistent with the idiosyncratic characteristics of the temporal lobe personality, while a non-dominant temporal lobe contribution has been proposed.
Keywords: Epilepsy; Seizures; Metaphor; Medicine in Literature; Research Report